2016
DOI: 10.3748/wjg.v22.i30.6776
|View full text |Cite
|
Sign up to set email alerts
|

New advances in targeted gastric cancer treatment

Abstract: Despite a decrease in incidence over past decades, gastric cancer remains a major global health problem. In the more recent period, survival has shown only minor improvement, despite significant advances in diagnostic techniques, surgical and chemotherapeutic approaches, the development of novel therapeutic agents and treatment by multidisciplinary teams. Because multiple genetic mutations, epigenetic alterations, and aberrant molecular signalling pathways are involved in the development of gastric cancers, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 189 publications
0
66
0
Order By: Relevance
“…However, the prognostic conditions of advanced cases remain undesirable. [2][3][4] It has been progressively realized that altered epigenetics, particularly changed DNA methylations are responsible for various kinds of carcinomas Iacobuzio-Donahue. [5][6][7] The process of inactivating anti-oncogenes, which participates in regulating cell cycles, DNA reparation as well as apoptosis is related to hypermethylated regulatory elements, which prevent transcriptional factors from binding to the corresponding recognition elements.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prognostic conditions of advanced cases remain undesirable. [2][3][4] It has been progressively realized that altered epigenetics, particularly changed DNA methylations are responsible for various kinds of carcinomas Iacobuzio-Donahue. [5][6][7] The process of inactivating anti-oncogenes, which participates in regulating cell cycles, DNA reparation as well as apoptosis is related to hypermethylated regulatory elements, which prevent transcriptional factors from binding to the corresponding recognition elements.…”
Section: Introductionmentioning
confidence: 99%
“…Although significant progress has been made in its diagnosis as well as in surgical combined adjuvant approaches, the outcomes of GC patients have only modestly improved [1]. In recent decades, considerable research has indicated that several signaling pathways are involved in gastric carcinogenesis and GC progression.…”
Section: Introductionmentioning
confidence: 99%
“…A number of monoclonal antibodies targeting different proteins, including EGFR, PD-1 (CD279), VEGF growth factor family, MET, and IGF-1R, are currently being tested and evaluated in clinical trials ( Table 1) [36][37][38][39].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%